Knowledge, Attitude and Behavior Related to Antibiotic Use in Community Dwellings - Rocci Jack Parse; Eva Mardiana Hidayat; Bachti Alisjahbana (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Irrational antibiotic use is the major reason for insidence of antibiotic resistance. Antibiotic misuse in community is influenced by environmental and behavioral factors. Environment included community preference for purchasing antibiotics, lack of health care infrastructure, lack of general practitioner and policy in regulating antibiotic use. Behavior is influenced by lack of information in antibiotic use and unawareness of antibiotic resistancy. The aim of the study was to assess the level of knowledge, attitude and behavior regarding antibiotic use in community dwellings.Methods: A cross sectional descriptive study was carried out to 96 respondents who were selected by a rapid survey sampling method in Cileles village Jatinangor, Sumedang, West Java, Indonesia in August 2013. Data were collected using questionnaires. The data was analyzed in the form of frequency and percentage.Results: Out of 96 respondents, only 40.6% had good knowledge regarding antibiotic use, 12.5% of respondents were prescribed antibiotics, but in the last course did not purchased all the antibiotics prescribed by the clinician and 55.2% of respondents did not complete their treatment course.Conclusions: Most of the community still have poor knowledge regarding antibiotic use and its consequences such as allergy, and resistancy based on the knowledge questions has a total score ≤6. Their attitude and behavior regarding antibiotic use are still poor which is also based on incompletion of the antibiotic treatment and irregular use.DOI: 10.15850/amj.v4n2.1082